2021
DOI: 10.1039/d1nr04352h
|View full text |Cite
|
Sign up to set email alerts
|

Culturing human iPSC-derived neural progenitor cells on nanowire arrays: mapping the impact of nanowire length and array pitch on proliferation, viability, and membrane deformation

Abstract: We tested the growth of human iPSC-derived NPCs on nanowire arrays across a wide range of array characteristics. The proliferation, viability, and interaction with the nanowire arrays were mapped depending on the array pitch and nanowire length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 112 publications
1
5
0
Order By: Relevance
“…It can be concluded that each individual BCSC is in close contact with each other on SiNWA due to the limited spreading area compared to the spreading area on the other two substrates. Besides, the mechanical strength and cell deformation are two most critical factors for cell differentiation 29 . Therefore, the cell deformation of BCSCs were stretched by an optical tweezer after 7 days incubation on different substrates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be concluded that each individual BCSC is in close contact with each other on SiNWA due to the limited spreading area compared to the spreading area on the other two substrates. Besides, the mechanical strength and cell deformation are two most critical factors for cell differentiation 29 . Therefore, the cell deformation of BCSCs were stretched by an optical tweezer after 7 days incubation on different substrates.…”
Section: Resultsmentioning
confidence: 99%
“…27 It was shown that geometric parameters and structural optimization of SiNWAs arrays are important signaling modes controlling cell adhesion, morphology, migration, proliferation, and differentiation by transporting exogenous cargos into cells without influencing the cell viability. 28 Harberts, et al 29 showed that SiNW arrays controlled the proliferation and differentiation of human iPSC-derived neural progenitor cells in correlation with the topological difficulty, for example, lengths. Chen, et al 21 reported that SiNW arrays induced the cellular deformations to facilitate gene delivery.…”
Section: Can Inducementioning
confidence: 99%
See 1 more Smart Citation
“…[ 25 ] In direct comparison to a prior study of us with undifferentiated neural progenitor cells (NPCs)—used to generate the neurons herein—the differentiated neurons were more likely to favor the fakir‐like state at similar specifications of the NW arrays. [ 75 ]…”
Section: Discussionmentioning
confidence: 99%
“…[25] In direct comparison to a prior study of us with undifferentiated neural progenitor cells (NPCs)-used to generate the neurons herein-the differentiated neurons were more likely to favor the fakir-like state at similar specifications of the NW arrays. [75] The neuronal differentiation yields on the NW arrays were analyzed after 14-15 days (8-9 on the NW arrays) of culturing by labeling neuron-specific markers such as MAP2, NeuN, and TH. About 65% of the cells cultivated on the NW arrays were positive for the postmitotic neuronal marker MAP2.…”
Section: Discussionmentioning
confidence: 99%